Twelve-month outcomes of MAKINGtheLINK: A cluster randomized controlled trial of a school-based program to facilitate help-seeking for substance use and mental health problems. (January 2020) - Lubman, Dan I; Cheetham, Ali; Sandral, Emma; Wolfe, Rory; Martin, Catherine; Blee, Fiona; Berridge, Bonita J; Jorm, Anthony F.; Wilson, Coralie; Allen, Nicholas B.; McKay-Brown, Lisa; Proimos, Jenny
Abstract: Background: Young people experiencing mental health problems are often reluctant to seek help, particularly from professionals (i.e., doctors or mental health workers). MAKINGtheLINK is a school-based intervention that aims to help adolescents overcome barriers to seeking professional help for mental health and substance use problems. Methods: A cluster randomised controlled trial was conducted to evaluate the 12-month outcomes of MAKINGtheLINK among 2447 participants (Mean age=14.9 years, SD=0.5 years, 50% male). Randomisation resulted in 1130 students from 11 schools allocated to receive the intervention, and 1317 students from 10 schools allocated to the wait-list control group. After the baseline assessment, follow-ups were conducted at 6-weeks ( n  = 2045), 6-months ( n  = 1874), and 12-months ( n  = 1827). The primary outcome measure was help-seeking behaviour, from both formal (e.g., health professionals) and informal (e.g., friends, family members) sources. The trial was registered with the Australia and New Zealand Clinical Trials Register (ANZCTR) on the 27th of February 2013 (registration number ACTRN12613000235707) Findings: The intervention was not associated with overall help-seeking at the 12-month follow-up ( p  = 0.99, odds ratio [OR]=1.00, 95% CI for OR = 0.70–1.42), or help-seeking for depression ( p  = 0.28, OR = 1.21, 95%CI =0.86–1.69), stress and anxiety ( p  = 0.73, OR = 1.04, 95%CI = 0.74–1.47), or alcohol/other drugs ( p  = 0.84, OR=1.12, CI=0.37–3.37). However, the intervention was associated with increased help-seeking from formal sources (compared to informal sources) both overall ( p   =  0.005, OR = 1.81, 95%CI = 1.19–2.75), as well as for depression ( p  = 0.01, OR=2.09, 95%CI=1.19–3.67), and stress and anxiety ( p < 0.006, OR = 1.72, 95%CI = 1.17–2.54). Interpretation: Rates of help-seeking remained unchanged following the intervention. However, MAKINGtheLINK effectively improved the quality of adolescent help-seeking behaviour by increasing help-seeking from formal sources. As prompt treatment is essential in reducing the long-term impact of early onset mental health problems, MAKINGtheLINK has the potential to make a significant contribution to existing early intervention and prevention efforts. Funding: National Health and Medical Research Council (APP1047492).